Interprofessional Strategies For Infection Prevention And Safe Clinical Practice: A Collaborative Study Among Dentistry, Nursing, Radiology, Operation Room, And Health Administration Professionals (The Review of Diabetic Studies, 2025)
The contemporary healthcare landscape is defined by increasing complexity, where the patient journey is rarely confined to a single clinical silo. A patient presenting with a dental abscess may require radiological imaging, surgical intervention in an operating theater, and post-operative nursing care, creating a continuum of exposure risks that transcends departmental boundaries. Healthcare-Associated Infections (HAIs) remain a recalcitrant challenge, contributing significantly to morbidity, mortality, and economic burden globally. While traditional Infection Prevention and Control (IPC) models have operated within professional domains—focusing on the specific mechanics of dentistry, the sterile field of surgery, or the isolation protocols of nursing—emerging evidence suggests this fragmented approach is insufficient. This comprehensive systematic review and operational analysis evaluates the efficacy of Interprofessional Education and Collaborative Practice (IPECP) in mitigating infection risks. By synthesizing data from diverse high-risk environments—including the aerosol-generating milieu of dentistry, the high-throughput diagnostic hub of radiology, and the sterile core of the operating room—this report proposes a unified, systems-based framework for safety. The analysis highlights that sustainable infection control is not merely a matter of individual adherence to protocol but a product of organizational culture, administrative governance, and engineered interdisciplinary workflows.